Re-Understanding the Sedimentary Environment of the Wufeng–Longmaxi Shales in the Sichuan Basin - Xiaoping Mao; Xiurong Chen; Fan Yang; Shuxian Li; Zhen Li; Yuexing Yang (Applied Sciences)
The current understanding of organic matter enrichment in marine shales remains highly controversial. Most scholars argue that deeper water environments and warmer climates facilitate the enrichment of organic matter. However, this perspective contradicts the principles of carbon sequestration in environmental science, necessitating a more in-depth discussion of its underlying mechanisms. This article utilizes the Wufeng–Longmaxi shales in the Sichuan Basin as a case study and integrates the primary productivity and carbon sequestration patterns observed in modern water bodies to analyze the processes governing organic matter enrichment in shales. The findings indicate that the Wufeng–Longmaxi shales in the Sichuan Basin did not form in a deep-water shelf environment during a period of large-scale transgression; rather, they developed in a highly enclosed shallow-water environment during a regressive phase. The proximity to ancient land correlates with higher organic matter abundance and gas production, suggesting that the mineralization model closely resembles that of coal, thereby highlighting the significance of proximity to land and the supply of terrigenous materials. It can be concluded that the depositional environment of organic-matter-rich marine shales is characterized by four key attributes: a shallow water depth, proximity to land (with a supply of terrestrial materials), a high enclosure, and a cold climate.